2015
DOI: 10.1016/j.rasd.2014.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between GSTT1 and GSTP1 allele variants as a risk modulating-factor for autism spectrum disorders

Abstract: We investigated the role of glutathione S-transferase (GST) genes in Autism Spectrum Disorder (ASD). We used data from 111 pairs of age- and sex-matched ASD cases and typically developing (TD) controls between 2–8 years of age from Jamaica to investigate the role of GST pi 1 (GSTP1), GST theta 1 (GSTT1), and GST mu 1 (GSTM1) polymorphisms in susceptibility to ASD. In univariable conditional logistic regression models we did not observe significant associations between ASD status and GSTT1, GSTM1, or GSTP1 geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 65 publications
2
25
0
Order By: Relevance
“…Over the years, many studies have attempted to elucidate triggering genetic factors in the development of ASD 4 , however, so far only several studies evaluated the possible association between GST polymorphisms, as independent factor (or in conjunction with environmental factors), and susceptibility to ASD 10,11,16,17 . Cytosolic GST family catalyzes the conjugation of electrophilic compounds, including products of oxidative stress, with GSH 9 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, many studies have attempted to elucidate triggering genetic factors in the development of ASD 4 , however, so far only several studies evaluated the possible association between GST polymorphisms, as independent factor (or in conjunction with environmental factors), and susceptibility to ASD 10,11,16,17 . Cytosolic GST family catalyzes the conjugation of electrophilic compounds, including products of oxidative stress, with GSH 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple lines of evidence which suggested that oxidative stress could represent the basis for the observed association between genetic, immunological and environmental factors underlying autism 13,1921 , also suggested the role of glutathione transferases in ASD development, in particular when taking into account the important antioxidant role of GSTs 11,17,22 .…”
Section: Introductionmentioning
confidence: 99%
“…For typically developing controls, we ruled out symptoms of ASD using the Social Communication Questionnaire (SCQ) Lifetime form (Rutter, Bailey, & Lord, 2003) with a cut-off score of 6, which is one standard deviation above the mean SCQ score for typically developing children (Mulligan, Richardson, Anney, & Gill, 2009). Details on the recruitment and assessment procedures of this study have been reported previously (Rahbar et al, 2012a; Rahbar et al, 2012b; Rahbar et al, 2013; Rahbar et al, 2014a; Rahbar et al, 2014b; Rahbar et al, 2014c; Rahbar et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…If the child had difficulty in spitting 2 mL of saliva, then the Oragene Discover OGR-575 for Assisted Collection with sponges was used (DNA Genotek). Saliva and whole blood samples (plasma, buffy coat, and red blood cell aliquots) were shipped from UWI to UTHealth for genetic analyses and details regarding DNA isolation and genotyping of GSTT1, GSTM1 , and GSTP1 were reported previously (Rahbar et al, 2014c; Rahbar et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…Recent findings from our Jamaican study of children with ASD and TD children revealed that the relationship between GSTP1 and blood arsenic concentrations varied by ASD status (TD or ASD) in an interactive model [42] In addition, we identified a significant gene-gene interaction between GSTP1 and GSTT1 in relation to ASD, where there was a significantly higher odds of ASD for children who were heterozygous for the GSTP1 Ile105Val polymorphism and had the GSTT1 null genotype (Matched Odds Ratio (MOR) = 2.97, 95% CI (1.09, 8.01), p = 0.03) [43]. Furthermore, we found a significant gene-environment interaction between GSTP1 and blood manganese concentrations (BMC) indicating that among children who had the Ile/Ile genotype for GSTP1 , those with BMC ≥ 12 µg/L had about four times higher odds of ASD than those with BMC < 12 µg/L ( p = 0.03) [44].…”
Section: Introductionmentioning
confidence: 99%